Effects of whole-body cryostimulation exposure in sport and medicine - Hausswirth, C. (ASPETAR Sports Medicine Journal, 2014)
The published studies concentrate on physiological, biochemical and haematological parameters affected by WBC. It reduces proinflammatory responses, decreases pro-oxidant molecular species and stabilises membranes, resulting in high potential beneficial effects on sports-induced haemolysis, and cell tissue damage, which is characteristic of heavy physical exercise. Conversely, it does not influence immulogical or hormonal responses, with the exception of testosterone, estradiol, noradrenaline and myocardial cell metabolism. Interleukin concentrations are modified by WBC, which induces anti-inflammatory responses.